2018
DOI: 10.3390/ijms19041036
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 and BMI1 Increase Pig Intestinal Epithelial Cell Proliferation by Stimulating WNT/β-Catenin Signaling

Abstract: Leucine-rich repeat-containing G protein-coupled receptor 5 (LGR5) and B-cell-specific Moloney murine leukemia virus insertion site 1 (BMI1) are markers of fast-cycling and quiescent intestinal stem cells, respectively. To determine the functions of these proteins in large animals, we investigated their effects on the proliferation of intestinal epithelial cells from pigs. Our results indicated that LGR5 and BMI1 are highly conserved proteins and that the pig proteins have greater homology with the human prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Members of SNHG family, including SNHG12, are supported to promote cancer development via regulating Wnt/b-catenin pathway (Feng et al, 2018;Shao et al, 2019;Song et al, 2019). As previously reported, BMI1 upregulation could activate Wnt pathway (Li et al, 2018a;Yu et al, 2018). Therefore, it is reasonable to suggest that SNHG12 contributed to stemness and EMT in ESCC cells through BMI/ Wnt/b-catenin pathway.…”
Section: Discussionmentioning
confidence: 62%
“…Members of SNHG family, including SNHG12, are supported to promote cancer development via regulating Wnt/b-catenin pathway (Feng et al, 2018;Shao et al, 2019;Song et al, 2019). As previously reported, BMI1 upregulation could activate Wnt pathway (Li et al, 2018a;Yu et al, 2018). Therefore, it is reasonable to suggest that SNHG12 contributed to stemness and EMT in ESCC cells through BMI/ Wnt/b-catenin pathway.…”
Section: Discussionmentioning
confidence: 62%
“…Wnt/β‐catenin pathway is required for maintaining the fate control of ISCs and plays an important role in initial villus formation (van der Flier & Clevers, 2009). A previous study has suggested that epithelial cell proliferation is stimulated by Wnt‐dependent mechanisms (X. G. Li et al, 2018; C. M. Li, Yan, Fu, Xu, & Wang, 2014). Besides, Wnt‐1 signaling inhibits apoptosis by activating β‐catenin/TCF‐mediated transcription, and active β‐catenin promotes cell survival by inhibiting Bax (S. Chen et al, 2001; Wang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…WNT/β-catenin/Tcf4 signaling pathway has been implicated in OPCs maturation and differentiation (21,67,70). In general, β-catenin does not accumulate in the cytoplasm under normal physiological condition because an existing complex consisting of AXIN2, APC, PP2A, GSK3, CK1α, could phosphorylate β-catenin (44). Subsequently, p-β-catenin is degraded by proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, p-β-catenin is degraded by proteasome. When the WNT/β-catenin/Tcf4 signaling pathway is activated, a large amount of β-catenin accumulates in the cytoplasm, and then binds to TCF4 in the nucleus to activate a series of downstream genes (44). Concurrently, AXIN2 expression is decreased which slows down the degradation of β-catenin.…”
Section: Discussionmentioning
confidence: 99%